ANALISIS IMPLEMENTASI KEBIJAKAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN (PNPM MP) STUDI KASUS DI KECAMATAN MANGGIS KABUPATEN KARANGASEM TAHUN 2009 DAN 2010 - Adi Tanaya, Nyoman Sura (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Poverty has been a classic, complex and global social symptom. Problemstructure: 1)Are the cultural elements the causes of the helplessness of the poor in Manggis District?2) Does the implementation management affect execution of the National Program forCommunity Empowerment Independent Rural Areas (PNPM MP) in Manggis District?3) Is the implementation of the PNPM PM policy able to empower the people inManggis District? 4) What is the meaning of the PNPM PM implementation at thedistrict, village and subvillage levels? Although the PNPM MP program implementationformally applies the bottom-up theory, the analytical PNPM MP implementationprocesses have shown a strong tendency to use the top-down theory. Theoretically, thePNPM MP program implementation in Manggis District has used the (Wayne Parsons,2005) combined approach. The Merilee Grindle implementation approach is able toexplain the PNPM MP implementation. By adding the communication factors to theGrindle model, the PNPM MPimplementation will resemble the bottom-up inclinedElmore model. Conclusion: first, the cultural factors represent one of the causes ofpoverty, but their impacts are relatively small compared with the natural and structuralfactors. Second, the policy managerial implementation has been successful in the sensethat it has performed all its functions, except for that of control and supervision. Third,the PNPM MP program implementation has complied with the applicable proceduresand provisions (PTO). The PNPM MP implementation has resulted in the capacityincreases of persons/institutions at Sub-district and District levels but has not succeededin reducing the number of the poor people (RTM). Fourth, the PNPM MPimplementation has in general complied with the procedures but the PNPM MPimplementation has not been able to reach the main purpose of the policy, to overcomethe problems of poverty.Key words: poverty, policy implementation, implementation models.